Sports injuries: a 5-year review of admissions at a major trauma center in the United Kingdom - Ahmad Hammad Hassan; Aref-Ali Gharooni; Harry Mee; James Geffner; Fahim Anwar (Journal of Trauma and Injury)
Purpose Sports offer several health benefits but are not free of injury risk. Activity dynamics vary across sports, impacting the injury profile and thereby influencing healthcare resource utilization and health outcomes. The purpose of this study was to investigate sports-related major trauma cases and compare differences across sports and activity groups. Methods A retrospective case notes review of sports-related major traumas over a 5-year period was conducted. Demographic, hospital episode-related, and health outcome-related data were analyzed, and differences were compared across sports and activity groups. The Glasgow Outcome Scale (GOS) at discharge was used as the primary outcome measure and the length of hospital stay as the secondary outcome measure. Results In total, 76% of cases had good recovery at discharge (GOS, 5), 19% had moderate disability (GOS, 4), and 5% had severe disability (GOS, 3). The mean length of hospital stay was 11.2 days (range, 1–121 days). The most severely injured body region was the limbs (29.1%) and vertebral/spinal injuries were most common (33%) in terms of location. A significant difference (P<0.05) existed in GOS across sports groups, with motor sports having the lowest GOS. However, no significant differences (P>0.05) were found in other health-outcome variables or injury patterns across sports or activity groups, although more competitive sports cases (67%) required admission than recreational sports cases (33%). Conclusions Spinal injuries are the most frequent sports injuries, bear the worst health outcomes, and warrant better preventive measures. Head injuries previously dominated the worst outcomes; this change is likely due to better preventive and management modalities. Competitive sports had a higher injury frequency than recreational sports, but no difference in health outcomes or injury patterns.